Perbandingan Efek Samping Propofol-Fentanil dan Propofol-Fentanil-Midazolam di Instalasi Medis Sentral Rumah Sakit X Bogor - Silvi Nurafni; Tri Desminingrum; Evida Mainanda (Fakultas Farmasi Universitas Pancasila, 2022)
Propofol is one of the most commonly used intravenous drugs employed to induce and maintain general anesthesia. The effective induction dose of propofol is 1.0-2.5 mg/kg IV caused hemodynamic instability significant as hypotension. Stability hemodynamic in used propofol can optimized with midazolam-fentanyl. The aims of this study was to determine the comparison of side effects propofol-fentanyl and propofol-fentanyl-midazolam in patient undergoing elective surgery with parameter of blood pressure, pulse, respiratory rate (RR). This study was a observational with prospective method in 60 patients undergoing elective surgery with physical status ASA I-II conducted in the period of April to July 2019. The result showed the induction anesthesia used of propofol-fentanyl caused decreased on systolic blood pressure 17,2±3 mmHg, diastolic blood pressure 5,3±1,6 mmHg, pulse 3,9±1,5 beats/minute, and RR 1,4±0,01 breaths/minute. The induction anesthesia used of propofol-fentanyl-midazolam caused decreased on systolic blood pressure 11,8±0,4 mmHg, diastolic blood preasure 4,2±0,4 mmHg, pulse value 5,0±0,9 beats/minute, and RR 2,8±0,9 breaths/minute. Side effects in the form of blood pressure, pulse and respiratory rate from the administration of the combination of propofol-fentanyl and propofol-fentanyl-midazolam were not significantly different.